Ergonomics in Mining: An Investigation on Occupational Safety in Indonesian Tin Mining - R. Priyoko Prayitnoadi; Glyn Lawson; Brendan Ryan; Setia Hermawati (Perhimpunan Ergonomi Indonesia, 2020)
This paper presents the results of a series of studies on participatory ergonomics (PE) in Indonesian tin mining. It describes an investigation into occupational safety and recommendation on how PE can be implemented. The study was conducted by postal data requests, interviews with participants including local government representatives, a tin company, and small-medium enterprises (SMEs). The study shows that support from OSH authorities is needed in order to strengthen workers’ knowledge in ergonomics and good safety practices and to allow them to implement ergonomics through training and the participatory approach. The results of this study may contribute to the implementation of PE. As a consequence of improved implementation, tin mining accidents may be reduced.